Uneven Development and Weltanschauung. Remarks on Lukács’ Late Writings on Marxism - Matteo Gargani (Lexicon Philosophicum, 2019)
From 1930 onwards, György Lukács considers ‘uneven development’ the typical relational form between economic progress and the corresponding evolution of other fields of human activity. In the early thirties Lukács focuses on the problem of elaborating an independent Marxist aesthetics, but then necessarily find himself having to deal with the general configuration of Marx’s alleged philosophy. The general theory illustrated in The Ontology of Social Being is where this philosophy, considered as a Weltanschauung, is given its final framework. His reflection on the ‘specificity’ of the aesthetic experience, as part of the broader framework of the main fields of art, science and everyday life, is the theoretical medium Lukács used in the fifties and sixties to fine-tune the need that had arisen decades earlier to attribute Marxism with genuine philosophical universality.